2010
DOI: 10.1108/14720701011085607
|View full text |Cite
|
Sign up to set email alerts
|

A new perspective on board composition and firm performance in an emerging market

Abstract: Purpose -This paper seeks to examine the relationship between board composition and firm performance using a board-level aggregation variable.Design/methodology/approach -This study uses linear regression to analyze the relationship between board role typology and firm performance using a panel data set of 277 non-financial listed Malaysian firms over the period 2002-2007.Findings -The empirical results show that firm-boards with a high representation of outside and foreign directors are associated with better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 28 publications
3
52
2
Order By: Relevance
“…Bédard et al 2004;Dhaliwal et al 2010;Klein 2002). Using Malaysian data, it is shown that companies with audit committees that comprise a high proportion of independent directors or that are fully independent have high quality accruals (Saleh et al 2007), performance (Ameer, Ramli & Zakaria 2009), and level of voluntary disclosure (Akhtaruddin & Haron 2010).…”
Section: Audit Committee Financial Expertisementioning
confidence: 99%
See 1 more Smart Citation
“…Bédard et al 2004;Dhaliwal et al 2010;Klein 2002). Using Malaysian data, it is shown that companies with audit committees that comprise a high proportion of independent directors or that are fully independent have high quality accruals (Saleh et al 2007), performance (Ameer, Ramli & Zakaria 2009), and level of voluntary disclosure (Akhtaruddin & Haron 2010).…”
Section: Audit Committee Financial Expertisementioning
confidence: 99%
“…In Malaysia, there is evidence indicating that only independent directors on the board perform greater monitoring (Ameer et al 2009). Using subsample analysis, we tested equation (1) and (2) by grouping our sample into two groups based on board independence.…”
Section: Additional Analysis Board Independencementioning
confidence: 99%
“…According to the theory, performance of BOD and the organization is different depending on the characteristics of decision making process. Even though there are controversies about the relationship between BOD and performances, many researchers provide evidences that BOD can make an impact on firm performance (Ameer et al , Dalton and Dalton , Davis et al , Jung et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Non-independent, non-executive directors (NEDs) and managerial ownership were found to be positively related to both dimensions of monitoring roles, while multiple directorships of NEDs were negatively related to management oversight roles. Boards with a high representation of outside and foreign directors were associated with better performance compared to those boards that have a majority of insider executive and affiliated NEDs (Ameer et al, 2010). Yammeesri and Herath (2010) reported that neither independent directors nor grey directors are significant determinants of improving firm value.…”
Section: Board Compositionmentioning
confidence: 99%